2017
DOI: 10.1177/1477153517713542
|View full text |Cite
|
Sign up to set email alerts
|

Light dominates colour preference when correlated colour temperature differs

Abstract: Colour preference of lighting is generally influenced by three kinds of contextual factors, which are the features of light, object and observer. In this study, a series of psychophysical experiments were conducted to investigate and compare the effect of certain factors on colour preference, including spectral power distribution of light, lighting application, observers' personal colour preference, regional cultural difference and gender difference. Certain LED lights with different correlated colour temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 52 publications
9
69
3
2
Order By: Relevance
“…As shown in Table 1, although different in magnitude, the results of the two experiments perfectly match each other in the form of the rank order (Spearman correlation coefficient r=1), which soundly proves the repeatability of this work. In addition, the inter-observer and intra-observer variability of Experiment 1 was also tested following the method used in the earlier work 15 and the results were also acceptable: the inter-observer variability was 1.26-1.89 (former study: 0.92-2.21) while the intra-observer variability was 13% (former study: 6%-17%). demonstrated that compared to the influence of the light, the influence of human factors turns out to be insignificant.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…As shown in Table 1, although different in magnitude, the results of the two experiments perfectly match each other in the form of the rank order (Spearman correlation coefficient r=1), which soundly proves the repeatability of this work. In addition, the inter-observer and intra-observer variability of Experiment 1 was also tested following the method used in the earlier work 15 and the results were also acceptable: the inter-observer variability was 1.26-1.89 (former study: 0.92-2.21) while the intra-observer variability was 13% (former study: 6%-17%). demonstrated that compared to the influence of the light, the influence of human factors turns out to be insignificant.…”
Section: Resultsmentioning
confidence: 91%
“…demonstrated that compared to the influence of the light, the influence of human factors turns out to be insignificant. 15 Based on such an opinion, a one-way Analysis of Variance (ANOVA) was used to investigate whether the absence of objects in the booth influenced the observers' preference rating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to confirm the excellent predictive performance of the new metric proposal, the experimental data of several different psychophysical studies on the perception of colour preference in metameric and multi-CCT lighting scenarios were collected (Jost-Boissard 2009, Jost-Boissard 2015, Wei 2014, Szabó 2016, Smet 2010a, VanRie 2009, Imai 2012, Imai 2013, Jost 2013, Tsukitani 2013, Lin 2016, Houser 2005, Huang 2018, Narendran 2002, Wang 2017) and a comprehensive meta correlation-analysis as proposed by Hunter and Schmidt (Hunter 2004) was eventually performed on these data to evaluate and compare the predictive power of the MCPI in terms of visual appreciation with those of other colour quality metrics. These included Sanders' preferred colour index (Sanders 1959a), Judd's flattery index .…”
Section: Results Of the Meta-correlation Analysismentioning
confidence: 99%
“…Their works proved that people did prefer the color rendition of white lighting at multiple correlated colour temperatures(CCTs) ranging from 2500 K to 5500 K, while they seemed to dislike colors that were illuminated by too cold CCT higher than 5500 K. The same group did two experiments, one involves evaluating color preferences for lighting with empty light box [8], to study color preferences for several LED white lights with different CCTs. The other studies the dominance of colour preference when the CCTs are different [9]. Lighting color preference is usually influenced by three environmental factors: light, object and observer.…”
mentioning
confidence: 99%